AKULAH JALAN, KEBENARAN DAN HIDUP - Mida Purba (Lembaga Penelitian STKIP Widya Yuwana, 2023)
Focus of this article is elaborating the meaning of the words of Jesus which we find in the gospel of John 14: 6 “I am the Way, the Truth and the Life”. The purpose is showing that a proper understanding regarding the meaning of the words of Jesus provides a way to know who Jesus is and to take a proper attitude towards it. Knowing him and accepting him continuously is the way to be mature in faith. In order to do that first, I elaborate a simple notion about what is prayer and what is not prayer, a relation with God. Second, I show that a human being essentially free to give and receive form of his or her life. Third, I point out the meaning of John 14: 6 “I am the Way, the Truth and the Life”. I end this article with a conclusion. The method that I used in doing this article is mystagogy.